Levels of heavy metals in green-lipped mussel Perna veridis (Linnaeus) from Muar Estuary, Johore, Malaysia - Yunus, Kamaruzzaman; Ong, Meng Chuan; Kasim, Zaleha; Saad, Shahbudin (Asian Network for Scientific Information, 2008)
Muscle and feather in tissue of 40 juveniles and 40 adult green-lipped mussel Perna veridis (L.) collected from Muar Estuary, Johor were analyzed for copper (Cu), cadmium (Cd), lead (Pb) and zinc (Zn) concentration using a fast and sensitive Inductively Coupled Plasma Mass Spectrometer (ICP-MS). In this study, the average concentration of Cu was 8.96 μg g-1 dry weights, Cd with 0.58 μg g-1 dry weight, Pb averaging 2.28 μg g-1 dry weights and Zn averaged to 86.73 μg g-1 dry weight. The highest accumulation of metal studied was found in feather sample compared to the muscle. The positive relationship of Cu, Cd, Pb and Zn with P. virdis length suggesting that the accumulation of these metals were formed in the mussel. In all cases, metal levels found were lower than the guideline of international standards of reference and the examined bivalve were not associated with enhanced metal content in their tissues and were safe within the limits for human consumption